Durable scalable 3D SLA‐printed cuff electrodes with high performance carbon + PEDOT:PSS‐based contacts. Issue 10 (2nd September 2022) - Doering, Onna Marie; Vetter, Christian; Alhawwash, Awadh; Horn, M. Ryne; Yoshida, Ken
Abstract: Background: The stimulation and recording performance of implanted neural interfaces are functions of the physical and electrical characteristics of the neural interface, its electrode material and structure. Therefore, rapid optimization of such characteristics is becoming critical in most clinical and research studies. This paper describes the development of an upgraded 3D printed cuff electrode shell design containing a novel intrinsically conductive polymer (ICP) for stimulation and recording of peripheral nerve fibers. Methods: A 3D stereolithography (SLA) printer was used to print a scalable, custom designed, C‐cuff electrode and I‐beam closure for accurate, rapid implementation. A novel contact consisting of a percolated carbon graphite base electrodeposited with an intrinsically conductive polymer (ICP), poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) produced a PEDOT:PSS + carbon black (CB) matrix that was used to form the electrochemical interface on the structure. Prototype device performance was tested both in‐vitro and in‐vivo for electrical chemical capacity, electrochemical interfacial impedance, surgical handling, and implantability. The in‐vivo work was performed on the sciatic nerve of 25 anesthetized Sprague Dawley rats to demonstrate recording and stimulating ability. Results: Prototypes of different spatial geometries and number of contacts (bipolar, tripolar, and tetrapolar) were designed. The design was successfully printed with inner diameters down to 500 μm. Standard bipolar and tripolar cuffs, with a 1.3 mm inner diameter (ID), 0.5 mm contact width, 1.0 mm pitch, and a 1.5 mm end distance were used for the functional tests. This geometry was appropriate for placement on the rat sciatic nerve and enabled in‐vivo testing in anesthetized rats. The contacts on the standard bipolar electrode had an area of 2.1 × 10 −2 cm 2 . Cyclic voltammetry on ICP coated and uncoated graphite contacts showed that the ICP increased the average charge storage capacity (CSC) by a factor of 30. The corresponding impedance at 1 Hz was slightly above 1 kΩ, a 99.99% decrease from 100 kΩ in the uncoated state. The statistical comparison of the pre‐ versus post‐stimulation impedance measurements were not significantly different ( p ‐value > 0.05). Conclusions: The new cuff electrode enables rapid development of cost‐effective functional stimulation devices targeting nerve bundles less than 1.0 mm in diameter. This allows for recording and modulation of a low‐frequency current targeted within the peripheral nervous system. Abstract : The C‐cuff is an upgraded 3D printed cuff electrode shell and I‐beam closure design containing a novel intrinsically conductive polymer (ICP). The new electrode allows for recording and modulation on targeted nerve bundles less than 1.0 mm in diameter within the peripheral nervous system. This cost‐effective and streamlined approach produces devices with comparable performance characteristics to current electrodes on the market for standard pulse stimulation, recording and extended low frequency performance to enable its use with low frequency stimulation.